2004
DOI: 10.1002/nag.389
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional simulation of fluid flow in X‐ray CT images of porous media

Abstract: SUMMARYA numerical scheme is developed in order to simulate fluid flow in three dimensional (3-D) microstructures. The governing equations for steady incompressible flow are solved using the semi-implicit method for pressure-linked equations (SIMPLE) finite difference scheme within a non-staggered grid system that represents the 3-D microstructure. This system allows solving the governing equations using only one computational cell. The numerical scheme is verified through simulating fluid flow in idealized 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…For example, x-ray tomographs of asphalt mix have been used to simulate three-dimensional fluid flow and estimate permeability in pavements. 29 The results indicated that the prior notions of a direct relationship between void volume fraction and permeability were incorrect. Microstructure-based simulations have also been used to determine the effect of processing on the thermal conductivity of thermal barrier coatings.…”
Section: Modeling Backgroundmentioning
confidence: 98%
“…For example, x-ray tomographs of asphalt mix have been used to simulate three-dimensional fluid flow and estimate permeability in pavements. 29 The results indicated that the prior notions of a direct relationship between void volume fraction and permeability were incorrect. Microstructure-based simulations have also been used to determine the effect of processing on the thermal conductivity of thermal barrier coatings.…”
Section: Modeling Backgroundmentioning
confidence: 98%
“…According to Adler et al (1990);Al-Omari and Masad (2004) and Masad et al (2000), the discrepancy between 2D and 3D computations can be attributed to the inherent limitation of a 2D computation in capturing the real 3D flow path in a highly heterogeneous material such as sand or clay, as well as to the difference in specific surface area between the discretized contours of the pore space and the real microstructure. Therefore, 2D computations can be improved by increasing the resolution of the images in order to capture the real specific surface.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies (Adler et al, 1990;Al-Omari and Masad, 2004;Blunt et al, 2013;Masad et al, 2000) the effective permeability of various porous materials (natural sandstones, carbonate reservoirs, asphalt pavements, sands, glass beads) was determined by solving the local equations of fluid flow. The microstructure was obtained directly from the sample by image processing, or idealized by utilizing statistical characteristics.…”
Section: Multiscale Modelling Of Fluid Flow In Geomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, interconnectivity is an important property of the air void phase in HMA mixture. However, previous studies have shown that the tortuosity of connected void paths in full dense mixtures is in a range of 3.16 and 4.94 [19]. Therefore, it is realistic to assume that the number of long connected paths within a 2-D slide of a mixture is negligible.…”
Section: Step 2: Creating a Set Of Air Voidsmentioning
confidence: 95%